Clinical Oral Condition Analysis and the Influence of Highly Active Antiretroviral Therapy on Human Salivary Microbial Community Diversity in HIV-Infected/AIDS Patients - Cao, Peilin; Zhang, Yifan; Dong, Guangyan; Wu, Hongkun; Yang, Yuxiang; Liu, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
The purpose of this study was to assess the clinical oral status and investigate the effect of highly active antiretroviral therapy (HAART) on oral flora diversity in human immunodeficiency virus (HIV)-infected/acquired immune deficiency syndrome (AIDS) patients. We first recorded and analyzed the demographic indicators of 108 HIV-infected patients and assessed their periodontal health, dental health and oral lesion status by oral examination. Besides, we compared the changes in salivary microbial communities of healthy controls, before and after treatment of HAART-processed AIDS patients by Roche 454 sequencing and RT-qPCR. In HIV-infected/AIDS patients, age, sex, marital status, income level, smoking and oral health behaviors had an effect on periodontal clinical indicators; age and marital status were correlated with dental clinical indicators; most of them were accompanied by oral manifestations, mainly including candidiasis albicans, salivary gland disease, AIDS-associated periodontitis, and oral ulcers. Besides, a total of 487 species were detected in the saliva of AIDS patients. The microbial communities of HAART-unprocessed AIDS patients significantly differed from those processed patients, with 112 unique microbial species. More importantly, a large number of conditioned pathogens were also detected in the saliva samples of AIDS patients, which may be associated with opportunistic infections. Therefore, HAART might have a crucial role in salivary microecological balance in AIDS patients. And these patients should pay attention to the maintenance of oral health, and the early initiation of HAART may be important for the development of oral lesions.